New molecules for solar cells - Pang, Jane Chieh Yu (2011)
New low band-gap donor materials with tunable energy levels for organic photovoltaics (OPV) by reduction of 4,8-di(2-thienyl)-benzo[1,2-c;4,5-c’]bis[1,2,5]thiadiazole (TBBT) to form pyrazino[2,3-g]quinoxaline (PQ) and [1,2,5]thiadiazole[3,4-g]quinoxaline (TQ) derivatives (as synthesized by Mr Tam Teck Lip and Dr Li Hairong) were characterized for their optical and electrochemical properties. Characterization of these derivatives was done by Matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometry, Thermal gravimetric analysis (TGA), Differential scanning calorimetry (DSC), Nuclear magnetic resonance (NMR) spectroscopy (1H, 13C), Ultraviolet-visible (UV-Vis) spectroscopy, Cyclic voltammetry (CV) and Polarised optical microscopy (POM). All the structures of the newly synthesized derivatives were confirmed by MALDI-TOF and NMR. Bandgaps calculated from UV-Vis plots match closely with values from CV. Bandgaps of derivatives that are stronger electron acceptors (BBT>TQ>PQ) were found to be lower and have a red shift in their absorption peaks in UV-Vis. A correlation study was carried out to help understand the relationship of these molecules based on their measured optical and electrochemical properties. This included correlating UV-Vis plots, CV plots, their corresponding melting points and POM images of crystal growth.